Computed Tomography Scan and ICD Interaction - Jose M. Porres; Jose L. Cerezuela; Oscar Luque; Pilar Marco (Case Reports in Medicine)
Although it has been considered a safe procedure, computed tomography scanning uses high doses of radiation and can cause malfunctioning in those patients with ICD when the radiation is directly incident on the device. We present a case of ventricular oversensing during a thoracic computed tomography.